2019
DOI: 10.3390/molecules24050913
|View full text |Cite
|
Sign up to set email alerts
|

The Extracts of Artemisia absinthium L. Suppress the Growth of Hepatocellular Carcinoma Cells through Induction of Apoptosis via Endoplasmic Reticulum Stress and Mitochondrial-Dependent Pathway

Abstract: Artemisia absinthium L. has pharmaceutical and medicinal effects such as antimicrobial, antiparasitic, hepatoprotective, and antioxidant activities. Here, we prepared A. absinthium ethanol extract (AAEE) and its subfractions including petroleum ether (AAEE-Pe) and ethyl acetate (AAEE-Ea) and investigated their antitumor effect on human hepatoma BEL-7404 cells and mouse hepatoma H22 cells. The cell viability of hepatoma cells was measured by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 32 publications
0
16
0
6
Order By: Relevance
“…Figure 5 indicated that the treatment of ATRA combined with BDMC has a higher activity of caspase-3 than that of ATRA alone at 48 hr. AB means ATRA combine with BDMC (Hirata et al, 2019;Wei et al, 2019) or to release AIF for causing cell apoptosis (Jung et al, 2018). The intrinsic apoptotic pathway is triggered due to the changes of Bak/Bcl-2 ratio for affecting the mitochondria membrane potentials, then leading to cytochrome c release and activation of caspase-9, and caspase-3 F I G U R E 4 The effects of ATRA, BDMC, and their combination on reactive oxygen species (ROS) and Ca 2+ productions and the levels of mitochondrial membrane potential (ΔΨ m ) in Hep3B cells.…”
Section: F I G U R Ementioning
confidence: 99%
See 1 more Smart Citation
“…Figure 5 indicated that the treatment of ATRA combined with BDMC has a higher activity of caspase-3 than that of ATRA alone at 48 hr. AB means ATRA combine with BDMC (Hirata et al, 2019;Wei et al, 2019) or to release AIF for causing cell apoptosis (Jung et al, 2018). The intrinsic apoptotic pathway is triggered due to the changes of Bak/Bcl-2 ratio for affecting the mitochondria membrane potentials, then leading to cytochrome c release and activation of caspase-9, and caspase-3 F I G U R E 4 The effects of ATRA, BDMC, and their combination on reactive oxygen species (ROS) and Ca 2+ productions and the levels of mitochondrial membrane potential (ΔΨ m ) in Hep3B cells.…”
Section: F I G U R Ementioning
confidence: 99%
“…Gels were transferred to a PVDF membrane and were incubated with primary antibody anti-BRCA-1, PARP, p-H2A.X, and MGMT (a); cyclin E, cyclin A, CDK2, and p21 (b); XIAP, AKT, FADD, Fas and FasL (c); Bid, Bcl-xl, Bcl-2, Bax, Bak, cytochrome c, and AIF (d); caspase-9 and -3 (e). AB means ATRA combine with BDMC (Hirata et al, 2019;Wei et al, 2019) or to release AIF for causing cell apoptosis (Jung et al, 2018). Based on these observations, we suggest ATRA combined with BDMC treatment induced apoptosis in Hep 3B cells via the mitochondria-dependent pathway.…”
Section: F I G U R Ementioning
confidence: 99%
“…La planta de ajenjo se ha empleado como remedio tradicional para tratar los casos de malas digestiones, pesadez de estómago y desarreglos intestinales, además de para estimular el apetito, limpiar el hígado y la vesícula biliar, favorecer la menstruación, y tratar el dolor de estómago, entre otros trastornos (Obón et al 2014). Recientemente, se han llevado a cabo estudios de bioactividad que ponen de manifiesto el potencial de esta especie y sus extractos como nematicidas (Liu et al 2019;Pino-Otín et al 2019), insecticidas (Guevara et al 2019), antifúngicos (Liu et al 2019;Rodríguez-Torres et al 2019) y anticancerígenos (Mughees et al 2019;Wei et al 2019).…”
Section: Introductionunclassified
“…They found that cell death was induced by the upregulation of autophagy markers and treatment in combination with doxorubicin enhanced its cytotoxicity (12). Wei et al have studied the anticancer activity of an ethanol extract from Artemisia absinthium and some subfractions on hepatocellular carcinoma cells [22]. The results showed the inhibition of cells growth and induction of apoptosis which might be mediated by the endoplasmic reticulum stress and mitochondrial-dependent pathway [22].…”
mentioning
confidence: 99%
“…Wei et al have studied the anticancer activity of an ethanol extract from Artemisia absinthium and some subfractions on hepatocellular carcinoma cells [22]. The results showed the inhibition of cells growth and induction of apoptosis which might be mediated by the endoplasmic reticulum stress and mitochondrial-dependent pathway [22]. In addition, it was demonstrated an inhibition of tumor growth in vivo using the H22 tumor mouse model (H22 cells were subcutaneously injected in male Kunming mice and tumor sizes were monitored over time).…”
mentioning
confidence: 99%